2009
DOI: 10.1007/978-3-642-01924-1_6
|View full text |Cite
|
Sign up to set email alerts
|

An Experience on Ada Programming Using On-Line Judging

Abstract: Abstract. Ada has proved to be one of the best languages to learn computer programming. Nevertheless, learning to program is difficult and when it is combined with lack of motivation by the students, dropout rates can reach up to 70%. In order to face up to this problem, we have developed a first-year course for computing majors on programming based on two key ideas: supplementing the final exam with a series of activities in a continuous evaluation context; and making those activities more appealing to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…So the students should test their work using unit tests and/or test files. The set of test cases have to be "well thought out" to avoid the false identification of programs [9]. It is also very important to use test cases covering every path throughout the program.…”
Section: Java Graders In Memoocmentioning
confidence: 99%
“…So the students should test their work using unit tests and/or test files. The set of test cases have to be "well thought out" to avoid the false identification of programs [9]. It is also very important to use test cases covering every path throughout the program.…”
Section: Java Graders In Memoocmentioning
confidence: 99%
“…Automated assessment systems for student database offer important benefits like instant feedback and consistency of the evaluation, and thus saving substantial time in the evaluation of the assignments. Some studies have also reported [3], [4] that immediate grades generate motivation and enthusiasm among students, although there are indications that this may differ as per various cultural [5].…”
Section: Type Problems With Traditional Assessmentmentioning
confidence: 99%
“…implantado con éxito como un sistema de aprendizaje y evaluación on-line en asignaturas de titulaciones de Informática (12,13,14).…”
Section: Enfermería Globalunclassified